Effect of Positive Thinking and Relaxation Program on Reducing Stress among Pregnant Adolescents - แซ่ตั้น ชุติกาญจน์; กาละ ศศิกานต์; ยังวนิชเศรษฐ สุนันทา (Princess of Naradhiwas University Journal, 2018)
The purpose of this quasi-experimental research was to examine the effect of positive thinking and relaxation program on reducing stress among pregnant adolescents. The sample consisted of 52 pregnant adolescents who attended the antenatal care in hospital, Southern part of Thailand. They were divided into a control group and an intervention group; twenty six pregnant adolescents per group. The intervention group received the positive thinking and relaxation program, while the control group received standard care. The intervention instrument consisted of positive thinking and relaxation program. The data collection tools comprised a personal data form and a stress questionnaire. All instruments in the study, except music CD, were content validated by three experts. The reliability of the stress questionnaire was examined using Cronbach’s alpha coefficient, yielding a value of .90. Data were analyzed using frequency, percentage, mean, standard deviation, chi squire, Wilcoxon Signed Ranks Test, and Mann-Whitney-U-test. The results were as follows: (1) the pregnant adolescents who received the positive thinking and relaxation program had significantly lower score of stress after intervention compared to before intervention (Z = 3.21, p < .01) and (2) the pregnant adolescents who received the positive thinking and relaxation program had significantly lower score of stress than that of pregnant adolescents who received standard care (Z = 4.98, p < .001). The results show the ability of positive thinking and relaxation program on reducing stress among pregnant adolescents. Therefore, the program should be applied to reduce stress for pregnant adolescents to promote well-being of mothers and their children.